Transitions into the futures: AI disruption and resilience in hospitality graduates - Georges El Hajal (Research in Hospitality Management)
This viewpoint article explores the impact of fast-paced advancements in artificial intelligence (AI) technologies on the hospitality industry’s workforce, focusing on the employability and career sustainability of today’s hospitality education graduates. AI technologies reshape traditional job roles and introduce new demands for resilience, adaptability and emotional intelligence. Hospitality graduates must develop human-centric skills and technical proficiency to ensure career sustainability. The article recommends revising hospitality curricula to incorporate digital literacy, emotional intelligence and lifelong learning, enabling graduates to thrive in a technology-driven future. Collaboration between educators and industry stakeholders is critical for preparing a resilient workforce to navigate ongoing technological disruptions.